Community-based participatory research for the assessment of health needs in Najran Health Cluster - Seham M. Eldeeb; Rashed S Alqudhaya; Salem A. Alsalem; Ali M. Alsalem; Alhassan M. Alhawkash; Zaid M. Alqureshah (Journal of Family and Community Medicine)
BACKGROUND: The health clusters are currently working toward becoming accountable care organizations responsible for the health status and healthcare needs of their population and for the value-based utilization of resources driven by the population health management (PHM). MATERIALS AND METHODS: In collaboration with the Health Holding Company and the Center for National Health Insurance, the Najran Health Cluster conducted its first 2024 community health needs assessment. Community-based participatory research was conducted using the quantitative and qualitative research methods. Quantitative research was based on the secondary data collection and analysis, whereas qualitative research engaged 229 participants in Focus Group Discussions. The PHM team analyzed this data to profile the community and identify the health needs of the population. RESULTS: Based on the health profile of the Najran health cluster, the main community health needs were identified: Accessing specialized healthcare services, improving school health programs and chronic disease prevention, enhancing physical activity and healthy food choices, smoking prevention, and minimizing the hazards of technology. CONCLUSION: Najran faces complex demographic and epidemiological transitions, that present challenges and opportunities for its healthcare system and society. Strategic planning and targeted interventions are essential for the fostering of a thriving community.